2009
DOI: 10.1007/bf03178329
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification of an antifungal protein produced byEnterococcus faecalis CHD 28.3

Abstract: -The antifungal protein produced by Enterococcus faecalis CHD 28.3 isolated from the Cheddar cheese was partially purified from the culture supernatant using ultrafiltration, anion exchange and gel filtration chromatography. Employing a 10 kDa cut off membrane, ultrafiltration of the culture supernatant resulted in a recovery of 44.6% of the antifungal protein with 1.7 fold increase in the specific activity. Anion-exchange chromatography using DEAE-Sepharose matrix followed by purification of the samples using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…The impact was concentrationdependent, as reflected by the inhibition zone diameters and CFS from E. faecalis isolated from Cheddar cheese (Ch9) have the highest effect. This is in context with Roy et al [25] who have shown that E. faecalis isolated from Cheddar cheese produce effective antifungal protein. These data are in agreement with others [11,18,25,26] who found that the identified E. faecalis non-haemolytic anticandida protein (ACP), might be developed as an effective treatment for candidiasis and its complications especially in immunocompromised individuals.…”
Section: Resultssupporting
confidence: 76%
“…The impact was concentrationdependent, as reflected by the inhibition zone diameters and CFS from E. faecalis isolated from Cheddar cheese (Ch9) have the highest effect. This is in context with Roy et al [25] who have shown that E. faecalis isolated from Cheddar cheese produce effective antifungal protein. These data are in agreement with others [11,18,25,26] who found that the identified E. faecalis non-haemolytic anticandida protein (ACP), might be developed as an effective treatment for candidiasis and its complications especially in immunocompromised individuals.…”
Section: Resultssupporting
confidence: 76%
“…Enterococcus spp. are rarely described to antifungal activities [12][13][14] 11 was reported to inhibit the growth of Fusarium culmorum and P. expansum [14].…”
Section: Resultsmentioning
confidence: 99%
“…LAB strains belonging to genus Enterococcus are rarely described to harbour antifungal activities (Roy et al . ; Shekh et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…These reactions on yeast's nucleus and vacuoles were observed and described also when yeast cells are submitted to strong stress by sonication or by heating (Webster and Watson 1993;Radel et al 2000). LAB strains belonging to genus Enterococcus are rarely described to harbour antifungal activities (Roy et al 2009;Shekh et al 2011). Enterococcus durans A5-11 was described as bacteriocinogenic and, as demonstrated in this article, has antagonistic effects against various fungal strains, including D. hansenii LMSA2.11.003, F. culmorum LMSA1.12.136, Candida krusei LMSA2.12.020, P. expansum LMSA1.08.102 and Penicillium roqueforti LMSA1.12.138.…”
Section: Changes Of Cell Ultrastructures Induced By Treatments With Cmentioning
confidence: 98%